2013
DOI: 10.2147/oajc.s44234
|View full text |Cite
|
Sign up to set email alerts
|

Women’s perceptions about reducing the frequency of monthly bleeding: results from a multinational survey

Abstract: Background:Monthly bleeding can have a negative impact on daily life and, given the choice, many women would reduce the frequency of bleeding. While some women choose to occasionally postpone or reduce bleeding frequency with an oral contraceptive (OC), most women have no or limited experience of regularly reducing the frequency of scheduled bleeding with OCs, ie, the extended OC regimen. Study design: An online survey of 4039 women aged 15-49 years who were currently using, had used, or would consider using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…As also found in Nigeria (Glasier et al 2003), Ghanaian women may prefer to menstruate regularly and any disturbance may cause anxiety. Similar concerns regarding reduced bleeding frequency associated with Studies in Family Planning 45(2) June 2014 pill use were found in a study in Europe, Latin America, and North America (Szarewski and Moeller 2013). Many women were worried about the possible health impact and thought that loss of menses was "unnatural."…”
Section: Components Of Unmet Need In 2008mentioning
confidence: 61%
“…As also found in Nigeria (Glasier et al 2003), Ghanaian women may prefer to menstruate regularly and any disturbance may cause anxiety. Similar concerns regarding reduced bleeding frequency associated with Studies in Family Planning 45(2) June 2014 pill use were found in a study in Europe, Latin America, and North America (Szarewski and Moeller 2013). Many women were worried about the possible health impact and thought that loss of menses was "unnatural."…”
Section: Components Of Unmet Need In 2008mentioning
confidence: 61%
“…Thirty-three studies had information pertinent to this topic, including six in Africa [ 43 , 47 , 87 , 104 , 107 , 122 ], nine in the Americas [ 44 , 46 , 57 , 103 , 133 137 ], five in Asia [ 45 , 63 , 64 , 83 , 114 ], nine in Europe [ 51 , 52 , 60 , 67 , 88 , 97 , 109 , 110 , 138 ], two in Oceania [ 106 , 139 ], and two in multi-country studies [ 50 , 140 ]. In studies across multiple countries, including Mali, Kenya, South Africa, Brazil, Spain, the Dominican Republic, Canada, the US, and the UK, regular menstruation was viewed by many women as a marker of health and fertility, as well as providing reassurance of not being pregnant [ 47 , 50 , 51 , 57 , 87 , 103 , 133 – 135 , 137 , 138 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies, primarily from higher-income countries, provided information specifically pertinent to how women perceive use of menstrual suppression in relation to health concerns [ 44 , 52 , 60 , 67 , 109 , 133 , 135 , 136 , 139 , 140 ]. The largest of these was an online survey of over 4000 women across eight countries (Brazil, Canada, the Czech Republic, France, Germany, Italy, the UK, and the US) [ 140 ]. Health concerns were substantial for women with respect to menstrual suppression, with 42% of women believing that postponing monthly bleeding would have negative effects on their health [ 140 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations